MODELAGEM MATEMÁTICA E CONTROLE ÓTIMO DE UM ATUADOR HIDRÁULICO CONSIDERANDO O EFEITO DO ATRITO DINÂMICO - Miotto, Fabiane E. M.; Valdiero, Antonio C.; Ritter, Carla S. (Salão do Conhecimento, 2013)
Resumo